Self-management socialism compared to social market economy in transition: Are there convergent paths? - Isa Mulaj (OrdnungsPolitisches Portal (OPO), 2009)
Despite considerable and miscellaneous research in transition economics, some of its aspects have yet to evolve and come up with a more standard theory. After the initial systemic change in two versions of socialist systems - centralist in the former Soviet Union (FSU), and self-management in the former Socialist Federal Republic of Yugoslavia (SFRY), and rush towards a market-based system, setbacks in economic performance were marked by a sharp decline in living standards for the majority of population. A soar in socio-economic trauma during economic transformation from self-management to a (full) market economy along with civil wars, has mostly hit the middle class bringing them around the poverty line. Although economic recovery and growth picked up after a decade of downturn to reach the pre-transition level, the rise in income differentiation has not changed much the situation of poverty which in the former SFRY countries (except Slovenia) remains widespread, whereas it has made a tiny minority better-off, namely private entrepreneurs, politicians and professionals. Yet, this polarisation may be natural after ownership transformation and privatisation in the short to medium run. But among majority who slide towards poverty, there were, and still are, nostalgic attitudes about economic welfare in the previous system. The pressure for more socially-oriented economic reforms has mainly come from this group, though policy makers too, were aware that this approach which is necessary to fix structural-adjustment problems, is more likely to be successful at aggregate level for sustainable and long term development, ceteris paribus. By looking back at the previous system and exploring current social and economic reforms in the former SFRY, this paper aims at investigating common points and theoretical convergences between self-management socialism and social market economy (SMEC) in line with the challenge of economic development.
Keywords: 330; SFRY; self-management socialism; transition; social market economy; development